Music in early childhood education as a tool in child's cognitive development (Research, Society and Development, 2020)
Music is a form of language that can develop skills that will be of fundamental importance for the child's development. In the school routine, music as an area of knowledge, with specific language characteristics, can expand knowledge through musical activities developed in the classroom, as it is within it that mediations and exchanges of experiences take place that help so much in the development child's cognitive function. Thus, it is necessary to demystify the idea that music at school is at the service of school calendar presentations / celebrations. Therefore, this research aimed to analyze the importance of music in early childhood education through the eyes of the teacher who works in this segment. The research collaborators were teachers at a public school in the municipality of Campo Verde - MT that attends early childhood education. Therefore, the research was carried out under a qualitative approach and the procedures adopted were field research, as well as bibliographic research. Content analysis was the technique used to perform the data analysis. Thus, it was concluded that music in early childhood education is an important and necessary tool for the development of cognitive, linguistic, psychomotor and socio-affective aspects, in addition to enabling the acquisition of new knowledge in a pleasant and fun environment, where the child feels stimulated and provoked to get involved and develop.